Training's Impact on Medical Staff's KAP in Infection Prevention for Nosocomial Viral Hepatitis B&C in Erbil Teaching Hospital's Hemodialysis Unit - Qasim Burhan Abdullah; Maaroof Tahseen Hassan; Sherzad Ali Ismael (Advanced Medical Journal)
Background & objectives: Hemodialysis patients are susceptible to various types of infections, such as exposure to blood borne pathogens. This study aims to identify the effects of training on the incidence of nosocomial viral hepatitis B & C infection and implement an interventional program to decrease the incidence of nosocomial infection.